2013
DOI: 10.1152/physiolgenomics.00023.2013
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of active cardiac remodeling genes in a familial hypertrophic cardiomyopathy mouse model rescued by a phospholamban knockout

Abstract: Rajan S, Pena JR, Jegga AG, Aronow BJ, Wolska BM, Wieczorek DF. Microarray analysis of active cardiac remodeling genes in a familial hypertrophic cardiomyopathy mouse model rescued by a phospholamban knockout. Physiol Genomics 45: 764 -773, 2013. First published June 25, 2013 doi:10.1152/physiolgenomics.00023.2013.-Familial hypertrophic cardiomyopathy (FHC) is a disease characterized by ventricular hypertrophy, fibrosis, and aberrant systolic and/or diastolic function. Our laboratories have previously develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hearts from wild-type or HCM C57BL/6 mice were excised at 2 months of age and subjected to transcriptome analysis. In the Tpm1 mutation model (GSE42892; Rajan et al, 2013 ), FVB/N mice overexpressed mouse Tpm1 containing a point mutation resulting in E180G (Tpm1-E180G). Hearts from wild-type or HCM FVB/N mice were excised at 4 months of age and subjected to transcriptome analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearts from wild-type or HCM C57BL/6 mice were excised at 2 months of age and subjected to transcriptome analysis. In the Tpm1 mutation model (GSE42892; Rajan et al, 2013 ), FVB/N mice overexpressed mouse Tpm1 containing a point mutation resulting in E180G (Tpm1-E180G). Hearts from wild-type or HCM FVB/N mice were excised at 4 months of age and subjected to transcriptome analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we sought to identify DEGs common to five different mouse models of HCM. The transcriptome datasets were downloaded from a public database ( Barrett et al, 2009 ) and were derived from mouse models of HCM caused by: (i) mutation of myosin heavy chain 6 ( Myh6 ) ( Luczak et al, 2011 ), (ii) mutation of Tpm1 ( Rajan et al, 2013 ), (iii) expressing human PLN on a null background ( Wang et al, 2011 ), (iv) KO of Fxn ( Huang et al, 2013 ), and (v) TAC, a model of pressure overload-induced HCM ( Lai et al, 2014 ). We identified five genes dysregulated in all five HCM transcriptome datasets, among which glutathione S-transferase kappa 1 ( Gstk1 ) was the only gene downregulated.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of FLT1 has been detected in cardiomyopathies by the NHLBI-Go Exome Sequencing Project (27); however, the association between this gene and HCM or DCM needs to be re-evaluated (28). Blood vessels serve important roles in the heart during cardiac disease and remodeling, and several vasculature-associate genes are involved in cardiac hypertrophy (29). DCM has the characteristics of cardiac enlargement and hypertrophy.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
“…To our knowledge, several proteomic and transcriptome profiling of HCM have been performed and a number of dysregulated genes have been identified before [ 20 23 ] (Additional file 3 ). For example, Lim et al identified 36 dysregulated genes involved in cytoskeletal proteins, protein synthesis, redox system, ion channels and those with unknown function in HCM [ 20 ].…”
Section: Discussionmentioning
confidence: 99%